Complications of Bone Plating Following Different Facial Bones Fractures - Al-Hammami, Ali R.; Al-Anee, Auday M.; Lateef, Thair Abdul; Al-khayat, Adil (European Scientific Journal, ESJ, 2018)
The Aim of our study was to evaluate the complication of bone plating fixation used for treatment of multiple type of facial fracture, reconstruction procedure and bone graft in maxillofacial trauma. This prospective study was performed on 42 patients to evaluates complications of the bone plates had been used in fixation of multiple facial fractures, between October 2013 and March 2015, The age of the patients ranged from 17 â€“ 65 years The mean age of the patients was (31.7Â± 9.4) years. There were 31 males and 11 females, with male to female ratio (2.81:1), patients were followed up for minimum 6 months. Seventy-one plates were inserted over 17 months. Among the 42 patients there were 45 fracture sites, 26 (57.8%) were mandibular fractures, 15 (33.3%) were ZMC fractures, and four (8.9%) were maxillary; it is worth mentioning that some patients had fracture at more than one site. Complications due to fracture fixation with bone plating were 33 represented 46.5% of the total 71 plates inserted, which included Infection/wound dehiscence 15 (21.1%), Discomfort/ palpability 9 (12.7%), Plate exposure 4 (5.6%), hardware failure (broken plate & loosening screw) 1 (1.4%), Cold/heat intolerance 3 (4.2%) and Pain (TMJ) account for one plate (1.4%). According to this study, there will be a need for hardware removal in a portion of patients treated with metallic osteosynthesis devices. This study states that the infection is most common reason for plate removal, followed by discomfort due to cold/heat climate, particularly in those facial regions that provide only thin soft tissue cover over the plate.